HFIP as a versatile solvent in resorcin[n]arene synthesis - Khosravi, Hormoz; Stevens, Valeria; Sánchez, Raúl Hernández (Beilstein Journal of Organic Chemistry, 2024)
Herein, we present 1,1,1,3,3,3-hexafluoroisopropanol (HFIP) as an efficient solvent for synthesizing resorcin[n]arenes in the presence of catalytic amounts of HCl at ambient temperature and within minutes. Remarkably, resorcinols with electron-withdrawing groups and halogens, which are reported in the literature as the most challenging precursors in this cyclization, are tolerated. This method leads to a variety of 2-substituted resorcin[n]arenes in a single synthetic step with isolated yields up to 98%.
Keywords: cavitand; cyclization; HFIP; hydroxyalkylation; resorcinarenes